1997
DOI: 10.1007/s004240050314
|View full text |Cite
|
Sign up to set email alerts
|

ATP regulates cardiac Ca 2+ channel activity via a mechanism independent of protein phosphorylation

Abstract: The role of adenosine triphosphate (ATP) in the regulation of L-type Ca2+ channel activity was investigated in inside-out patches from guinea-pig ventricular cells, in which the Ca2+ channel activity had been reprimed by application of cytoplasm from bovine heart. Passing the cytoplasm through a diethylaminoethyl (DEAE)-sepharose column or heating at 60 degrees C for 20 min attenuated the induction Ca2+ channel activity to 6-13% of that in the preceding cell-attached patch. Addition of 10 mM MgATP to the cytop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 31 publications
3
36
1
Order By: Relevance
“…The latter mechanism has been shown to operate for K ATP and I Ca regulation (33,35). In our case, neither the non-hydrolysable analogue of ATP AMP-PCP nor GTP prevented the I HERG run-down caused by ATP depletion (Fig.…”
Section: Glycolysis-derived Atp May Be Responsible For Maintaining Thmentioning
confidence: 67%
“…The latter mechanism has been shown to operate for K ATP and I Ca regulation (33,35). In our case, neither the non-hydrolysable analogue of ATP AMP-PCP nor GTP prevented the I HERG run-down caused by ATP depletion (Fig.…”
Section: Glycolysis-derived Atp May Be Responsible For Maintaining Thmentioning
confidence: 67%
“…In contrast, the persistent increase requires ATP and, perhaps, ATP-dependent phosphorylation, since the L-type currents ran down within minutes in the presence of NaUTP. ATP has been reported to regulate cardiac L-type channels by phosphorylation-dependent and -independent mechanisms (4,61). Whatever the mechanism, addition of ATP (5-20 mM) to the pipette has been reported to delay Ca 2ϩ channel rundown (28).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular ATP has been shown to modulate the activity of voltage-activated Ca 2ϩ channels by phosphorylation-dependent and -independent mechanisms (4,61). We compared the effects of MgATP (5 and 10 mM) and UTP (5 mM) on the time-dependent expression of the noninactivating, presumed L-type Ca 2ϩ currents in AZF cells.…”
Section: Voltage-gated Camentioning
confidence: 99%
“…We used 10 M CSL and 1.22 M CaM, which were submaximum concentrations for the channel-repriming effects, together with 3 mM ATP in all of the inside-out patch experiments. ATP was necessary to induce channel activity (19,22,23). In the previous studies, it has been reported that ATP supports channel activity by a mechanism independent of protein phosphorylation but not fully understood (22,23).…”
Section: Calpastatin Domain L Suppresses Cav12 Channel Activity In Tmentioning
confidence: 99%